Analysis of the influence of laser irradiation on the accumulation of biomass and polysaccharides pleurotus ostreatus (JACQ.) Р. Kumm - Reshetnyk, Kateryna (ScienceRise: Biological Science, 2020)
The aim of the study was to investigate the effect of laser irradiation of mycelium on the amount of biomass and synthesis of P. ostreatus polysaccharides. Materials and methods. For the study, 6 strains of P. ostreatus from the Collection of cultures of basidiomycetes of the Department of Botany and Ecology of Vasyl Stus DonNU were used. A device consisting of LED lasers was used for laser irradiation of vegetative mycelium: BRP – 3010–5, with red spectrum radiation with a wavelength of 635 nm; BBP – 3010–5 with blue spectrum radiation with a wavelength of 405 nm and BGP – 3010–5 with green spectrum radiation with a wavelength of 532 nm. The level of biomass accumulation was determined by weight. The polysaccharide content was determined by the phenol-sulfur method. Results. The most effective was green light irradiation with a wavelength of 532 nm. For strain P-192 – the amount of biomass increased by 71.4 %. For strains P-191 and P-155 biomass increased by 60 % and 53.5 %. For strains P-108, P-154 and P-6v, the amount of biomass increased from 33.3 to 50 %. For strain P-192, the amount of mycelial endopolysaccharides increased by 42.0 %. For strains P-191 and P-6v, the amount of endopolysaccharides increased by 39.3 % and 38.7 %. For strains P-108, P-155 and P-154 the amount of mycelium endopolysaccharides increased from 30.7 % to 35.8. For strain P-192 the content of exopolysaccharides increased by 30.5 %. For strains P-154 and P-191, the amount of exopolysaccharides increased by 28.1 % and 27.8 %. For strains P-108, P-155 and P-6v the content of exopolysaccharides increased from 24.6 % to 25.8 %. Conclusions. The most effective mode of photoactivation of P. ostreatus mycelium for obtaining target products was determined. In particular, the best response was observed in response to green light with a wavelength of 532 nm for strain P-192 – the amount of biomass increased by 71.4 %, the amount of mycelium endopolysaccharides increased by 42.0 %, and the content of exopolysaccharides increased by 30.5 %